Pharmaceutical Policy in Countries with Developing Healthcare Systems - Babar, Zaheer-Ud-Din (Springer International Publishing : Imprint: Adis, 2017)
A comprehensive and granular insight into the challenges of promoting rational medicine, this book serves as an essential resource for health policy makers and researchers interested in national medicines policies. Country-specific chapters have a common format, beginning with an overview of the health system and regulatory and policy environments, before discussing the difficulties in maintaining a medicines supply system, challenges in ensuring access to affordable medicines and issues impacting on rational medicine use. Numerous case studies are also used to highlight key issues and each chapter concludes with country-specific solutions to the issues raised. Written by highly regarded academics, the book includes countries in Africa, Asia, Europe, the Middle East and South America.
Keywords: Pharmacy.; Public health.; elektronické knihy; electronic books